CHILDHOOD IN BLUEY: AN INVITATION FOR CHILDREN AND ADULTS TO CO-EXPERIENCE OTHER FORMATIVE RELATIONSHIPS - Farias, Juliana Marques de; Almeida, Alessandra Londero; Ourique, Maiane Liana Hatschbach (Literatura em Debate, 2025)
This article reflects on children's thinking expressed through play as an invitation for children and adults to co-experience their understanding of the world. The aim is to analyze the image of childhood presented in the animated series Bluey and the tensions it creates in the organization of early childhood teachers' work. The discussion is structured around three dimensions: play taken seriously, play as the integration of experiences, and play across different ages. It is observed that Bluey represents a powerful device that challenges crystallized representations of childhood and can inspire sensitive and contextualized teaching practices, emerging within the time of children's experiences with the world around them.